'Jeotgalicoccus saudimassiliensis' sp. nov., a new bacterial species isolated from air samples in the urban environment of Makkah, Saudi Arabia. (January 2017) - Papadioti, A.; Azhar, E.I.; Bibi, F.; Jiman-Fatani, A.; Aboushoushah, S.M.; Yasir, M.; Raoult, D.; Angelakis, E.
Abstract: We report here the main characteristics of 'Jeotgalicoccus saudimassiliensis' strain 13MG44_air T (CSUR P1221), a new species of the Jeotgalicoccus genus that was isolated from air samples in the city environment of Makkah, Saudi Arabia, during the pilgrim period of Hajj 2012.